Question about Computers & Internet

Ad

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of.(from cars to computers, handyman, and even drones)

click here to download the app (for users in the US for now) and get all the help you need.

Goodluck!

Posted on Jan 02, 2017

Ad

SOURCE: four years ago allan was three less than twice

Allan is 19 and Roy is 13.

Solution:

First we have 2 variables, their ages: I used Allan = x & Roy = y

Equation 1: X - 4 = 2*(Y-4) - 3

We can ignore the 5 years in the second part of the statement. Allan will always be 6 years older than Roy whether it be 5 years from now or ten years form now.

Equation 2: X = Y + 6

Substitute Y + 6 for X in equation 1:

X - 4 = 2*(Y-4) - 3 becomes Y + 6 - 4 = 2*(Y-4) - 3

That simplifies to Y + 2 = 2Y - 8 - 3

Rewrite it again: Y + 2 = 2Y - 11

Add 11 to both sides: Y + 13 = 2Y

Subtract Y from both sides: 13 = Y

Now plug 13 in for y in Equation 2

X = Y + 6

X = 13 + 6

X = 19

Posted on Oct 09, 2009

Ad

SOURCE: one year ago pandit was three times his sister's

test email mama heta udeta yanawa.

Posted on Dec 24, 2010

SOURCE: Father is 3 times as

So the father is 3 times as old as his daughter.

Let F represent the age of the fatherLet D represet the age of the daughter

So we know from the first sentence,

F = 3 * D

From the second sentence, 12 years from now the father is 1 year les than twice his daughters age,

First, lets assume it's not 12 years from now (to avoid confusion), we would haveF + 1= 2 * D

But since its 12 years from now, we have to add 12 to both ages

(F + 12) + 1 = 2 * (D + 12)

Let's simplify a bit,

F + 13 = 2 * D + 24F = 2D + 11

Now we have to solve these two equations together, we can plug the first equation into the second,

F = 3 * DF = 2 * D + 11

3 * D = 2 * D + 11D = 11

So the daughter is 11 years old, we can find out how old the father is by plugging into the first equation

F = 3 * DF = 3 * 11F = 33

So the father is 33 and the daughter is 11.

Posted on Jul 19, 2011

SOURCE: Jan is twice as old

Jan is 48 years old and Jake is 24 years old.

(Jan - N, Jake - K
N=2K
N+K=5K-48
N+K+48=5K
N+48=4K
N+48=2N
48=N
K=N/2=48/2=24)

Thanks, that was fun.

Posted on Jul 26, 2011

Let m be Marian's age, d Diana's age and c Carlos age.

I hope I helped :)

- sum of ages is 17: m+d+c=17
- two years from now Marian will be twice as old as Diana: m+2=2*(d+2) so m+2=2d+4 so 2d=m-2 or d=(m-2)/2=m/2-1
- Carlos will be half as old as Marian 4 years from now: c+4=1/2(m+4) or c+4=m/2+2 or c=m/2-2
- now: m+d+c=m+m/2-1+m/2-2=17
- 2m=17+3=20
- m=20/2=10 years
- d=m/2-1=5-1=4 years
- c=m/2-2=5-2=3 years

I hope I helped :)

Sep 18, 2011 | Office Equipment & Supplies

Let the brother's age be x:

16years for Mary = 4x years for Brother

From equation: 4x = 16

x = 4

Therefore, the brother is 4 years old.

__Mary__ __ Brother__

16 4

After 4 years +__4 4__

20 8

After the next 4 years +__4 4__

24 12

24 is twice as old as 12; therefore for the sister to be twice as old as brother she will 24years when her brother is 12 years.

Or by calculation;

If 4 is the age for the brother, when the sister is 16, and y years will pass for the to be such that the sister is twice as old as the brother, then;

16 + y = 2(4 + y)

16 + y = 8 + 2y

16 - 8 = 2y - y

8 = y

Therefore, 8 years elapse before the sister is twice as old as the brother.

Sister will be: (16 + 8) = 24years

Brother will be: (4 + 8) = 12years

16years for Mary = 4x years for Brother

From equation: 4x = 16

x = 4

Therefore, the brother is 4 years old.

16 4

After 4 years +

20 8

After the next 4 years +

24 12

24 is twice as old as 12; therefore for the sister to be twice as old as brother she will 24years when her brother is 12 years.

Or by calculation;

If 4 is the age for the brother, when the sister is 16, and y years will pass for the to be such that the sister is twice as old as the brother, then;

16 + y = 2(4 + y)

16 + y = 8 + 2y

16 - 8 = 2y - y

8 = y

Therefore, 8 years elapse before the sister is twice as old as the brother.

Sister will be: (16 + 8) = 24years

Brother will be: (4 + 8) = 12years

Aug 02, 2011 | Computers & Internet

Jan is 48 years old and Jake is 24 years old.

(Jan - N, Jake - K N=2K N+K=5K-48 N+K+48=5K N+48=4K N+48=2N 48=N K=N/2=48/2=24)

Thanks, that was fun.

(Jan - N, Jake - K N=2K N+K=5K-48 N+K+48=5K N+48=4K N+48=2N 48=N K=N/2=48/2=24)

Thanks, that was fun.

Jul 26, 2011 | Washing Machines

So the father is 3 times as old as his daughter.

Let F represent the age of the fatherLet D represet the age of the daughter

So we know from the first sentence,

F = 3 * D

From the second sentence, 12 years from now the father is 1 year les than twice his daughters age,

First, lets assume it's not 12 years from now (to avoid confusion), we would haveF + 1= 2 * D

But since its 12 years from now, we have to add 12 to both ages

(F + 12) + 1 = 2 * (D + 12)

Let's simplify a bit,

F + 13 = 2 * D + 24F = 2D + 11

Now we have to solve these two equations together, we can plug the first equation into the second,

F = 3 * DF = 2 * D + 11

3 * D = 2 * D + 11D = 11

So the daughter is 11 years old, we can find out how old the father is by plugging into the first equation

F = 3 * DF = 3 * 11F = 33

So the father is 33 and the daughter is 11.

Let F represent the age of the fatherLet D represet the age of the daughter

So we know from the first sentence,

F = 3 * D

From the second sentence, 12 years from now the father is 1 year les than twice his daughters age,

First, lets assume it's not 12 years from now (to avoid confusion), we would haveF + 1= 2 * D

But since its 12 years from now, we have to add 12 to both ages

(F + 12) + 1 = 2 * (D + 12)

Let's simplify a bit,

F + 13 = 2 * D + 24F = 2D + 11

Now we have to solve these two equations together, we can plug the first equation into the second,

F = 3 * DF = 2 * D + 11

3 * D = 2 * D + 11D = 11

So the daughter is 11 years old, we can find out how old the father is by plugging into the first equation

F = 3 * DF = 3 * 11F = 33

So the father is 33 and the daughter is 11.

Jul 19, 2011 | Computers & Internet

No answer available - Barry isn't mentioned in the equation, and there are four people mentioned in the question.

Apr 05, 2011 | Computers & Internet

Within 11 years, the age of Peter will be half the square of the age he was 13 years ago. Calculate the current age of Peter.

Suzy is ten years older than Billy, and next year she will be twice as old as Billy. How old are they now?

Suzy is ten years older than Billy, and next year she will be twice as old as Billy. How old are they now?

Sep 22, 2010 | Computers & Internet

(D=Dad's age, and S=Son's age)

D=S+20 (Dad is 20 years older than Son)

D+10 = 2xS (In ten years Dad will be twice Son's current age)

therefore (by substitution):

S+20+10 = 2xS

S+30 = 2S

2S = S+30

2S-S = 30 (subtract S from both sides)

D = S+20

D = 30+20

In ten years, Dad will be 60, which is twice Son's current age of 30.

Please ask for -Gort.

Aug 27, 2010 | Mathsoft Solving and Optimization...

Hi,

Let the present age of the Rodney = X

present Age of the Jasmin = Y

As per the Situation,

Y-9 = 2 (X - 9)

Y-9 = 2X - 18

Y = 2X - 18 +9

Y = 2X-9

Second,

X + Y = 45

Y = 45 - X

Taking Both the situations,

2X - 9 = 45 - X

3X = 54

X = 54/3 = 18

Y = 45 - 18 = 27

Hence,

Age of Jasmin = 27

Let me know, if needed further assistance.

Hope i helped you.

Thanks for using ' Fixya ' and have a nice day!!

Let the present age of the Rodney = X

present Age of the Jasmin = Y

As per the Situation,

Y-9 = 2 (X - 9)

Y-9 = 2X - 18

Y = 2X - 18 +9

Y = 2X-9

Second,

X + Y = 45

Y = 45 - X

Taking Both the situations,

2X - 9 = 45 - X

3X = 54

X = 54/3 = 18

Y = 45 - 18 = 27

Hence,

Age of Jasmin = 27

Let me know, if needed further assistance.

Hope i helped you.

Thanks for using ' Fixya ' and have a nice day!!

Mar 17, 2010 | Disney Watches

how to remove contents locks

May 01, 2009 | T-Mobile Wingâ„˘ Smartphone

Edwin is 14. Ruel is 7.

In 3 years Edwin will be 17. Edwin will be 10. (3*10 - 13 = 17)

Let x=Ruel's age now, and 2x=Edwin's age now.

2x+3=3(x+3)-13

2x+3=3x+9-13

2x+3=3x-4

2x+7=3x

7=x

If you are going to post these, the least you could do is rate them as Fixya. :-) Thanks!

In 3 years Edwin will be 17. Edwin will be 10. (3*10 - 13 = 17)

Let x=Ruel's age now, and 2x=Edwin's age now.

2x+3=3(x+3)-13

2x+3=3x+9-13

2x+3=3x-4

2x+7=3x

7=x

If you are going to post these, the least you could do is rate them as Fixya. :-) Thanks!

Dec 11, 2008 | Computers & Internet

Nov 22, 2017 | Computers & Internet

58 people viewed this question

Usually answered in minutes!

×